2013
DOI: 10.1186/1476-511x-12-24
|View full text |Cite
|
Sign up to set email alerts
|

SCARB1 single nucleotide polymorphism (rs5888) is associated with serum lipid profile and myocardial infarction in an age- and gender-dependent manner

Abstract: BackgroundMutation in SCARB1 gene, exon 8 rs5888, has been associated with altered lipid levels and cardiovascular risk in humans though the results have been inconsistent. We analysed the impact of SCARB1 single nucleotide polymorphism (SNP) rs5888 with plasma lipid profile and association with coronary artery disease (CAD) in a Lithuanian population characterized by high morbidity and mortality from CAD and high prevalence of hypercholesterolemia.MethodsThe study included 1976 subjects from a random sample (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 33 publications
4
31
1
Order By: Relevance
“…One of the single nucleotide polymorphisms (SNPs) in the SCARB1 gene is rs5888 SNP, which was initially found by Acton 17, a “C” to “T” substitution at cDNA position 1050 base position on exon 8. The rs5888 SNP T allele has been associated with increased serum HDL-C levels and decreased risk of atherosclerosis related diseases 24-28. In our previous studies, however, we found that the rs5888 SNP T allele was associated with decreased HDL-C levels and increased TC, LDL-C and ApoB levels in three Guangxi populations 29,30.…”
Section: Introductioncontrasting
confidence: 51%
See 1 more Smart Citation
“…One of the single nucleotide polymorphisms (SNPs) in the SCARB1 gene is rs5888 SNP, which was initially found by Acton 17, a “C” to “T” substitution at cDNA position 1050 base position on exon 8. The rs5888 SNP T allele has been associated with increased serum HDL-C levels and decreased risk of atherosclerosis related diseases 24-28. In our previous studies, however, we found that the rs5888 SNP T allele was associated with decreased HDL-C levels and increased TC, LDL-C and ApoB levels in three Guangxi populations 29,30.…”
Section: Introductioncontrasting
confidence: 51%
“…In LDL receptor-deficient mice, attenuated expression of SCARB1 was associated with increased LDL-C and accelerated atherosclerosis 14,15. The association of several variants in the SCARB1 gene and serum lipid profiles has been reported in diverse populations 16-28. One of the single nucleotide polymorphisms (SNPs) in the SCARB1 gene is rs5888 SNP, which was initially found by Acton 17, a “C” to “T” substitution at cDNA position 1050 base position on exon 8.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that lipid-associated loci arestrongly associated with other components of the metabolic syndrome, including SBP and DBP with excess associations of 2.5-fold and 3.7-fold[5], respectively. We ignored the possible modulation of gene-age interactions by gender[16-17]and adjusted for the use of lipid-altering medications through a dichotomous (yes/no) covariate; this crude adjustment ignored both the dosage (which is not available in this study) and exact medication taken.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that a rare T variant was associated with an atheroprotective lipid profile in men but not in women [9,13]. A previous study carried out in Lithuania revealed that men aged 65–74 who were carriers of the TT genotype had a higher level of HDL-C and a lower risk of myocardial infarction as compared to the CC genotype [31]. Gender and age-specific effects on blood lipid profiles were also demonstrated by other investigators [12,13,15].…”
Section: Discussionmentioning
confidence: 99%